Why is Son Preference so Persistent in East and South Asia? A Cross-Country Study of China, India, and the Republic of Korea - Das Gupta, Monica; Zhenghua, Jiang; Bohua, Li; Zhenming, Xie; Chung, Woojin; Hwa-Ok, Bae (World Bank, Washington, DC, 2014)
Son preference has persisted in the face of sweeping economic and social changes in China, India, and the Republic of Korea. The authors attribute this to their similar family systems, which generate strong disincentives to raise daughters while valuing adult women's contributions to the household. Urbanization, female education, and employment can only slowly change these incentives without more direct efforts by the state and civil society to increase the flexibility of the kinship system such that daughters and sons can be perceived as being more equally valuable. Much can be done to this end through social movements, legislation, and the mass media.